Prophylactic administration of rosmarinic acid ameliorates depression-associated cardiac abnormalities in Wistar rats: Evidence of serotonergic, oxidative, and inflammatory pathways - Verma H.; Shivavedi N.; Tej G.N.V.C.; Kumar M.; Nayak P.K. (My University, 2025)
Psychiatric disorders and associated cardiac comorbidities have increased the risk of mortality worldwide. Researchers reported that depression increases the possibility of future cardiac abnormalities by approximately 30%. Therefore, there is an unmet need to develop therapeutic interventions to treat depression and associated cardiac abnormalities. The present study was conducted to evaluate the prophylactic effect of rosmarinic acid (RA) against chronic unpredictable stress (CUS)-induced depression associated cardiac abnormalities in Wistar rats. The CUS paradigm, which comprised several stressors, was employed for 40 days to induce depressive-like behavior and associated cardiac abnormalities in rats. Along with CUS, RA at a dose of 25 and 50 mg/kg was administered orally to two groups of animals for 40 days. Behavioral tests (forced swim test and sucrose consumption test) and molecular biomarkers (corticosterone and serotonin) were performed. Electrocardiography was performed before CUS (Day 0), Day 20, and Day 40 to study electrocardiogram parameters. Furthermore, changes in body weight, organ weight, tissue lipid peroxidation, glutathione, catalase, cTn-I, MMP-2, and proinflammatory cytokines (TNF-α and IL-6) were estimated. Our results showed that RA treatment caused a reduction in immobility period, adrenal hyperplasia, corticosterone level, tissue lipid peroxidation, cTn-I, MMP-2, proinflammatory cytokines, and QRS complex duration, while an increase in sucrose consumption, brain serotonin level, T-wave width, glutathione, and catalase activity as compared with the CUS-control group. The results of our study proved that RA administration ameliorates CUS-induced depression-associated cardiac abnormalities in rats via serotonergic, oxidative, and inflammatory pathways. © 2022 Wiley Periodicals LLC.